DAMPAK INVASI RUSIA TERHADAP REAKSI PASAR PADA PERUSAHAAN SEKTOR PERTAMBANGAN DI INDONESIA - Muhammad Afdhal; Indra Basir; Muhammad Agung Mubarak (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2022)
This study aims to determine and analyze the impact of the Russian invasion of Ukraine on market reactions to mining sector companies in Indonesia. This research was conducted by examining the market reaction of the period before and after the Russian invasion of Ukraine on February 24, 2022. The market reaction in this study was calculated through abnormal stock returns using the single index model method. The research data were analyzed using the paired sample t-test. The results of this study reveal that there are differences in abnormal returns between before and after the Russian invasion of Ukraine on February 24, 2022. These results indicate that investors in the mining sector were reactive in the early period of the Russian invasion of Ukraine on companies in Indonesia.